Populärmusiken under 1950-talet - Ling, Jan (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2025)
The 1950’s were one of the most important periods of change for popular music in Sweden. Previously under the main influence of German ”Schlager” and their social atmosphere of middle class sophistication, Swedish popular music now became dominated by rock’n’ roll with its social base among the younger working class generation. The dimensions of this change can be compared to these brought about by Islamic culture in the Balkans and Spain during the Middle Ages. One of the most positive dynamic consequences of the change was the increase of interest in active musicianship, especially among the younger working class generation. This interest, mainly restricted to playing the guitar and to singing, also helped to renew traditional popular song, not infrequently at an ironic distance. However, rock’n’ roll tended to lead to a kind of satellite culture, whose main ambition seemed to be the most faithful possible emulation of American idols. Unfortunately, schools in Sweden have always neglected music on their curriculum. Moreover the Swedish folk music revival of the late 60’s had not yet occurred. Thus Swedish mass media companies were able to market ”folksey” singers whose qualities were more connected to aspects of their personality and presentation rather than musical merits. Words and music drew on the sentimental clichés and village pump nostalgia of earlier broadsides and ballads. The culture shock of musical change in Sweden during the 1950’s teaches us that we need to study both the function and the ideological impact of popular music in order to provide other musical conditions for its existence than those offered by transnational capitalist corporations.